Asosiasi Makroalga pada Ekosistem Lamun di Perairan Pantai Samuh, Nusa Dua, Bali - Gaina, Jublina Pauleta Veralda Nari Maku; Giri Putra, I Nyoman; Wiyanto, Dwi Budi (Journal of Marine Research and Technology, 2024)
Macroalgae are photosynthetic organisms living in the intertidal area, which is vital in supporting the primary productivity of coastal ecosystems. The need for similar resources (e.g., light, nutrients, space) between macroalgae and seagrass is likely to trigger competition between the two. Thus, this study aims to determine the species composition, species density, and associations between macroalgae and seagrass in the waters of Samuh Beach. This research was conducted in October – December 2023. Observation of macroalgae and seagrass samples used the quadratic transect technique with a size of 50×50 cm. Data analysis was done by calculating the composition, density, and association of macroalgae and seagrass types. This study found 26 species of macroalgae and 8 species of seagrasses. The macroalgae with the highest species composition is Padina australis, with a percentage of 16% and a species density value of 1.56 ? ind/m ? ^2.Meanwhile, species that have the lowest composition were Avrainvillea erecta, Callophyllis haenophylla, Dictyopteris delicatula, and Galaxaura, with a percentage of 1% and a species density of 0.15 ? ind/m ? ^2. The seagrass with the highest species composition in the waters of Samuh Beach is Cymodocea rotundata, with a percentage of 33% and a density of 200.7 ? ind/m ? ^2. Meanwhile, seagrasses that have the lowest species composition were Cymodocea serrulata and Halodule uninervis, with a percentage of 2% and density of 10.2 ? ind/m ? ^2 and 10.3 ? ind/m ? ^2, respectively. Most of the macroalgae and seagrass found in Samuh Beach were not associated with each other.